Voltammetric Determination of Phosphate in Brazilian Biodiesel Using Two Different Electrodes - Torrezani, Larissa; Saczk, Adelir Aparecida; de Oliveira, Marcelo Firmino; Stradiotto, Nelson Ramos [UNESP]; Okumura, Leonardo Luiz (Wiley-Blackwell, 2011)
The presence of contaminants, such as phosphate, in biodiesel, has several drawbacks for instance: current engines perform poorly, fuel tanks deteriorate, catalytic conversion is damaged, and particles emission is increased. Therefore, biodiesel quality control is extremely important for biodiesel acceptance and commercialization worldwide. In this context, a bare glassy carbon electrode (GCE) and another chemically modified electrode with iron hexacyanoferrate (Prussian Blue - PB) were developed for determination of phosphate in biodiesel. The LODs of 6.44 and 1.19 mg kg(-1), and LOQs of 21.43 and 3.97 mg kg(-1) were obtained for the bare GCE and the PB-modified GCE, respectively. The methodology was employed for analysis of Brazilian biodiesel samples, and it led to satisfactory results, demonstrating its potential application for biodiesel quality control. Additionally, recovery and interference tests were conducted, which revealed that the developed methods are suitable for analysis of phosphate in biodiesel samples.
Keywords: Brazilian biodiesel; Voltammetric analysis; Phosphate